2014
DOI: 10.1007/s11357-014-9714-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of quadriceps strength and handgrip strength in their association with health outcomes in older adults in primary care

Abstract: Sarcopenia is thought to play a major role in the functional impairment that occurs with old age. In clinical practice, sarcopenia is often determined by measuring handgrip strength. Here, we compared the lower limb quadriceps strength to the handgrip strength in their association with health outcomes in older adults in primary care. Our study population consisted of older adults (n=764, 68.2 % women, median age 83) that participated in the Integrated Systemic Care for Older People (ISCOPE) study. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 32 publications
5
50
2
2
Order By: Relevance
“…The correlation between handgrip strength and QoL is in accordance with other studies [6, 32, 33]. As handgrip strength is an overall measurement of body strength in older adults [34, 35], our results indicate that muscle strength is an important factor for QoL, whereas muscle mass is not.…”
Section: Discussionsupporting
confidence: 92%
“…The correlation between handgrip strength and QoL is in accordance with other studies [6, 32, 33]. As handgrip strength is an overall measurement of body strength in older adults [34, 35], our results indicate that muscle strength is an important factor for QoL, whereas muscle mass is not.…”
Section: Discussionsupporting
confidence: 92%
“…Older people with slow gait speed have been found to be at an increased risk of subsequent disability, falls, cognitive decline, hospitalization, and mortality, as well as stroke and heart failure [47][48][49][50]. Grip strength has been recommended as the most practical method of measuring muscle strength which can predict the measured health outcomes while quadriceps strength can not [51]. Grip strength showed an association with quality of life, disability, mortality, hospitalization [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Grip strength has been recommended as the most practical method of measuring muscle strength which can predict the measured health outcomes while quadriceps strength can not [51]. Grip strength showed an association with quality of life, disability, mortality, hospitalization [51][52][53]. Many studies have shown that ACEIs have favorable effect on physical function.…”
Section: Discussionmentioning
confidence: 99%
“…Chan et al reported that quadriceps strength and handgrip strength (HS) were independently associated with health outcomes at baseline, including quality of life, disability in daily living, hospitalization, and gait speed 23. The measurements could also aid in the identification of older adults in primary care with the poorest health outcomes.…”
Section: Methodsmentioning
confidence: 99%